2008
DOI: 10.1590/s0104-42302008000400018
|View full text |Cite
|
Sign up to set email alerts
|

Influência da atividade física programada na pressão arterial de idosos hipertensos sob tratamento não-farmacológico

Abstract: RESUMOOBJETIVO. Avaliar a influência da atividade física na pressão arterial de pacientes idosos hipertensos sob tratamento não-farmacológico (TNF). MÉTODOS.Estudamos homens e mulheres, maiores de 60 anos, com hipertensão arterial estágio I, sem uso de antihipertensivos. Os pacientes foram randomizados em dois grupos: GRUPO CONTROLE (GC) -orientados para TNF; e GRUPO ESTUDO (GE) -TNF e programa de atividade física supervisionada que consistia de três sessões semanais com uma hora cada. A duração do estudo foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
25

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
2
9
0
25
Order By: Relevance
“…Our data demonstrated that physical exercise during the intervention period was sufficient to maintain the pressure levels, not being observed significant differences in the inter-group and intra-group evaluation after tem weeks of regular physical exercise, corroborating the results found by Marceau et al 13 and Barroso et al 14 , in which medication was substituted for exercise. In the study by Marceau et al 13 ten-week periods of exercise with intensities range from 50% and 70% of VO 2max were used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data demonstrated that physical exercise during the intervention period was sufficient to maintain the pressure levels, not being observed significant differences in the inter-group and intra-group evaluation after tem weeks of regular physical exercise, corroborating the results found by Marceau et al 13 and Barroso et al 14 , in which medication was substituted for exercise. In the study by Marceau et al 13 ten-week periods of exercise with intensities range from 50% and 70% of VO 2max were used.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Marceau et al 13 ten-week periods of exercise with intensities range from 50% and 70% of VO 2max were used. In the casual measurement, BP alteration was not observed after training at any intensity, while Barroso et al 14 found initial and final pressure values similar to the ones reported by us. Aerobic and resistance exercises were performed; in spite of the more prolonged duration, after six months of intervention significant pressure reduction was not demonstrated.…”
Section: Discussionsupporting
confidence: 85%
“…The findings in this research evidence data of high concern, since regular practice of physical activity is a protective behavior for the development of obesity, cardiovascular diseases, type II diabetes, colon cancer 16 and hypertension 17 , besides contributing to the improvement of wellness sensation 18 . The practice of physical activities favors social interaction, improves self-assuredness (belief of the individual in his/her capacity to perform specific tasks) and provides higher sensation of control over the events and demands of the environment.…”
Section: Discussionmentioning
confidence: 71%
“…A prática de EF pode contribuir para diminuir o uso de diuréticos em pacientes com hipertensão arterial 27 . Além dos benefícios ao curso da doença, a prática também pode contribuir para a redução do peso, fator que é fortemente relacionado à presença de hipertensão arterial 28 . Desse modo, o exercício físico e a adoção de hábitos saudáveis, como abstenção de alimentos gordurosos, diminuição do sal nos preparos, minimização no uso de álcool e abandono do tabagismo, poderiam contribuir de maneira significativa para diminuir a frequência de IU, principalmente entre idosos menos ativos.…”
Section: Discussionunclassified